Models and Effectiveness of Structured Discharge Planning in the Poststroke Care Transition: A Systematic Literature Review - Imanuella Imanuella; Azzahra Sida Puspaningrum; Ragil Yunila; Ika Nur Pratiwi (Jurnal Sehat Indonesia (JUSINDO), 2026)
The transition of care from hospital to home among post-stroke patients is a critical phase associated with risks of functional decline, rehospitalization, and increased caregiver burden. However, limited studies specifically examine the core components of structured discharge planning and its effectiveness across different healthcare contexts. This research aims to synthesize recent evidence on discharge planning models and their effects on post-stroke outcomes, including functional independence, quality of life, rehospitalization, and caregiver-related outcomes. A Systematic Literature Review was conducted following PRISMA 2020 guidelines, with searches in PubMed, Scopus, ProQuest, SAGE, and ScienceDirect for studies published between 2020 and 2025. A total of 22 studies met the inclusion criteria from an initial 641 articles and were analyzed using a narrative-thematic approach. The results indicate that most studies demonstrate high methodological quality, with three main findings: variations in discharge planning models (ESD, TCM, family-based, and telehealth), the central role of nurses in coordination and education, and positive outcomes such as improved activities of daily living, quality of life, self-efficacy, and caregiver resilience, as well as reduced readmission and psychological distress. In conclusion, structured and collaborative discharge planning involving family support is effective in improving transitional care quality, although variations in interventions and outcomes should be considered when interpreting the findings.